Gothic Horror as the Representation of Childhood Trauma in Gaiman's The Ocean at the End of the Lane - Dhini, Ania Rahma; Haryanti, Rahayu Puji (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study aims to analyze how the elements of gothic horror in Neil Gaiman's The Ocean at the End of the Lane represent the childhood trauma of the main character (narrator). The background of this research is the lack of studies specifically discussing the role of gothic horror elements as symbols of psychological wounds in contemporary literary narratives. This research uses a qualitative approach with Cathy Caruth's trauma theory, which views trauma as an experience that is not fully understood when it occurs, but rather comes back in the form of nightmares, flashbacks, and memory fragments. Primary data sources were obtained from the novel, while secondary data were obtained from journal articles, books, and previous research. The data collection technique was done through close reading to identify the story's gothic horror elements and traumatic experiences. The results show that the three elements of gothic horror in this novel, such as the gloomy setting and the feeling of alienation, the evil figure of Ursula Monkton, and the distortion of time and space, function as a reflection of the narrator's childhood trauma, such as loneliness, loss, betrayal, and helplessness. In addition to creating a creepy atmosphere, these elements convey the narrator's psychological state of feeling insecure, ununderstood, and bereft of shelter. The novel shows that the emotional wounds that a person experiences as a child can be embedded in their memories and affect their lives as adults by using gothic elements in the story. The main conclusion is that the gothic horror elements in this novel serve as a way to convey psychological suffering that is difficult to express directly. It also shows that gothic literature can be a means of reflection on the long-term impact of childhood trauma.